Arecae pericarpium water extract alleviates chronic pancreatitis by deactivating pancreatic stellate cells - Kweon, Bitna; Kim, Dong-Uk; Oh, Jin-Young; Oh, Hyuncheol; Kim, Youn-Chul; Mun, Yeun-Ja; Bae, Gi-Sang; Park, Sung-Joo (Frontiers in Pharmacology, 2022)
Chronic pancreatitis (CP) is a chronic inflammatory disease of the pancreas with irreversible morphological changes. Arecae pericarpium (ARP), known to improve gastrointestinal disorders, has not yet been reported to inhibit fibrosis in CP. Therefore, we investigated the beneficial effects of ARP on cerulein-induced CP. Cerulein (50 μg/kg) was administered intraperitoneally to mice every hour, six times a day, four times a week for a total of three weeks to induce CP. To ascertain the prophylactic effects of ARP, ARP water extract (50, 100, or 200 mg/kg) or saline was administered intraperitoneally 1 h before the onset of CP. To determine the therapeutic effects of ARP, ARP water extract (200 mg/kg) or saline was administered for a total of two weeks, starting one week after the onset of CP. The pancreas was collected immediately for histological analysis. Additionally, to determine the effectiveness and mechanism of ARP in alleviating pancreatic fibrosis, pancreatic stellate cells (PSCs) were isolated. ARP treatment considerably improved glandular atrophy and inflammation and repressed collagen deposition in the pancreas. Furthermore, ARP water extract inhibited extracellular matrix (ECM) constituents such as alpha-smooth muscle actin (α-SMA), collagen I, and fibronectin 1 (FN1) in pancreatic tissue and PSCs. ARP also suppressed transforming growth factor-β (TGF-β) signaling by inhibiting SMAD2 phosphorylation. Our study suggests that ARP exhibits anti-fibrotic effects in cerulein-induced CP by inhibiting TGF-β/SMAD signaling.